Assessing Student Attitudes Regarding Cost-Consciousness in Medical Education - Marisa Leon-Carlyle; Rory McQuillan; Ioana Baiu; Amy Sullivan; Dmitry Dukhovny; Neel Shah (MedEdPublish, 2019)
Purpose: The purpose of this study was to compare attitudes regarding cost-consciousness between student populations at two medical schools in the United States and Canada.